General synthesis of 2D rare-earth oxide single crystals with tailorable facets. Issue 5 (23rd August 2021) - Li, Linyang; Lu, Fangyun; Xiong, Wenqi; Ding, Yu; Lu, Yangyi; Xiao, Yao; Tong, Xin; Wang, Yao; Jia, Shuangfeng; Wang, Jianbo; Mendes, Rafael G; Rümmeli, Mark H; et al.
Abstract: Two-dimensional (2D) rare-earth oxides (REOs) are a large family of materials with various intriguing applications and precise facet control is essential for investigating new properties in the 2D limit. However, a bottleneck remains with regard to obtaining their 2D single crystals with specific facets because of the intrinsic non-layered structure and disparate thermodynamic stability of different facets. Herein, for the first time, we achieve the synthesis of a wide variety of high-quality 2D REO single crystals with tailorable facets via designing a hard-soft-acid-base couple for controlling the 2D nucleation of the predetermined facets and adjusting the growth mode and direction of crystals. Also, the facet-related magnetic properties of 2D REO single crystals were revealed. Our approach provides a foundation for further exploring other facet-dependent properties and various applications of 2D REO, as well as inspiration for the precise growth of other non-layered 2D materials. Abstract : The synthesis of a wide variety of high-quality 2D rare-earth oxide single crystals with tailorable facets is achieved via designing a hard-soft-acid-base couple for controlling the 2D nucleation and growth of the predetermined facets.